Komunikasi dalam Implementasi Kebijakan Pendidikan Wajib Belajar 9 Tahun di Kecamatan Ngadiluwih - Ahmad Khoirul Syani; Sohibul Mufid; Mufarrihul Hazin (Khazanah Pendidikan, 2017)
AbstractThe Government recognizes the need to improve the quality of education as a tool toimprove the quality of human resources. One of them through government policyrequires basic education in order to achieve competitiveness of resources. This studyaims to find out how this policy is implemented in an area in the aspect ofcommunication and socialization. The method used is through qualitative descriptiveapproach. The data collection technique is done by interview, observation anddocumentation, data analysis used by data condensation, data display, and conclusion,data validity is done by checking credibility, dependency, and confirmability. Theresults of this study indicate that 100% of children in Ngadiluwih who graduated fromprimary school went to the next level, and the drop out rate in junior high school onlyreached 0.6%.Keywords: education policy, Compulsory Learning, communication.